Sustained censorship in VE (2026-05) (Venezuela) - Voidly (2026)
CRITICAL severity censorship detected in Venezuela. Confidence: 77%. Data sourced from OONI.
Censorship Incident ID: VE-2026-0408
Keywords: censorship; VE; censorship; critical